Incidence and Durability of SARS-CoV-2 Antibodies in Patients with Cancer and Health Care Workers following the First Wave of the Pandemic. (19th February 2022) - Lai, Catherine; Potosky, Arnold L.; McGuire, Colleen; Lobo, Tania; Ahn, Jaeil; Haddad, Bassem R.; Richards, Ernest W.; Anand, Palka; Wright, Kristen; Christenson, Robert H.; Boyle, Lisa; Goy, Andre; et al.
Abstract : Background . Patients with cancer and health care workers (HCW) are at higher risk for SARS-CoV-2 infection. There are limited data regarding the rate of symptomatic versus asymptomatic infection and subsequent seropositivity in both populations. Methods . We performed a prospective study of patients and HCW across two institutions during the first wave of the pandemic to analyze the prevalence of SARS-CoV-2 antibodies, the extent of associated symptoms, and durability of serologic response. Results . In 1, 953 persons (733 patients and 1, 220 HCW), overall seropositivity rates for 3.1% patients (95% CI 2.0–4.7) and 3.7% HCW (95% CI 2.7–4.9, p = 0.520 ), were similar. Each institutions' seropositivity rates were numerically higher in HCW than patients. Non-Hispanic Whites and Asians had lower antibody rates (2.8%, 95% CI 2.0–3.8 and 3.3%, 95% CI 1.2–7.0) compared to Hispanics (6.9%, 95% CI 3.4–12.4) and non-Hispanic Blacks (5.9%, 95% CI 3.3–9.7), p < 0.001 . Among persons with a positive SARS-CoV-2 antibody, 87% of patients and 56% of HCW did not recall having had a fever. Among HCW, administrative and technical personnel were most likely to be seropositive. The rate of persistent seropositivity at 3 months was similar between patients and HCW and was not influenced by the reporting of fever, cancer type, or therapy. Conclusion . These data suggest that patients are not at higher risk for febrile SARS-CoV-2 infections or more transient immunity than HCWs. Furthermore, racial differences and lack of association with the extent of HCW contact with COVID-19 patients suggest that community rather than hospital virus exposure was a source of many infections.